C*-algebras and Elliptic Theory - Bojarski, Bogdan; Mishchenko, Alexander S.; Troitsky, Evgenij V.; Weber, Andrzej (Trends in Mathematics, 2006)
This volume contains the proceedings of the conference on "C*-algebras and Elliptic Theory" held in Bedlewo, Poland, in February 2004. It consists of original research papers and expository articles focussing on index theory and topology of manifolds. The collection offers a cross-section of significant recent advances in several fields, the main subject being K-theory (of C*-algebras, equivariant K-theory). A number of papers is related to the index theory of pseudodifferential operators on singular manifolds (with boundaries, corners) or open manifolds. Further topics are Hopf cyclic cohomology, geometry of foliations, residue theory, Fredholm pairs and others. The wide spectrum of subjects reflects the diverse directions of research emanating from the Atiyah-Singer index theorem. Contributors: B. Bojarski, J. Brodzki, D. Burghelea, A. Connes, J. Eichhorn, T. Fack, S. Haller, Yu.A. Kordyukov, V. Manuilov, V. Nazaikinskii, G.A. Niblo, F. Nicola, I.M. Nikonov, V. Nistor, L. Rodino, A. Savin, V.V. Sharko, G.I. Sharygin, B. Sternin, K. Thomsen, E.V. Troitsky, E. Vasseli, A. Weber .